Fatality assessment for high pressure reactor of methanol production plantsfrom CO2 hydrogenation / Mohd Aizad Ahmad and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Abdul Rashid, Zulkifli (Universiti Teknologi MARA Shah Alam, 2019)
New technology emerges for carbon dioxide hydrogenation where captured carbon dioxide reacts with hydrogen for methanol production using high pressure condition up to 442 bar. The research on high pressure process focus on how much percentage of carbon dioxide and hydrogen converted, accompanied with how much percentage of methanol selectivity. There is no comprehensive study on safety, especially in term of consequences to human fatalities if incident occurred at this highpressure plant. Therefore, the purpose of this paper is to assess percentage of fatalities occur for reactor methanol (MeOH) plant operates at high pressure of 442 bar. It studies the possibility on (i) various events occurred in term of toxicity, thermal radiation, and overpressure; and (ii) estimation of percentage of fatalities when all that events occurred in comparison with reference plant operating at reactor pressure of 76 bar. Process plant is simulated using HYSYS and the obtained mass density of mixture, mass fraction, and volume fraction of chemical are used to calculate amount of toxicity (ppm), thermal radiation (kW/m2 ), and overpressure (psi) using consequence model simulated in ALOHA software. Threat zones generated by ALOHA software are then exported to the MARPLOT software to observe the area affected by the case study. The studied methanol reactor releases chemical mixture consists of hydrogen, carbon dioxide, MeOH, carbon monoxide (CO), and water, which only water is not considered as hazardous material. The release of chemical mixture observed for 10 mm, 25 mm, and 160 mm leakage, simulated at day and night conditions. The result for plant that operates at pressure of 442 bar has the highest severity of 44% fatality, which comes from the event of flammable methanol jet fire at daytime, leakage of 160 mm hole size. Meanwhile, for plant operating at 76 bar, the highest fatality is 27%, occurred from toxicity release of carbon dioxide at nighttime, leakage of 160 mm hole size.